2022
DOI: 10.1021/acs.analchem.2c00600
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Biocatalytic System for Biosensing by Combining Metal–Organic Framework (MOF)-Based Nanozymes and G-Quadruplex (G4)-DNAzymes

Abstract: A high catalytic efficiency associated to a robust chemical structure are among the ultimate goals when developing new biocatalytic systems for biosensing applications. To get ever closer to these goals, we report here on a combination of metal-organic framework (MOF)-based nanozymes and G-quadruplex (G4)-based catalytic system known as G4-DNAzyme. This approach aims at combining the advantages of both partners (chiefly, the robustness of the former, the modularity of the latter). To this end, we used MIL-53(F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…It is well-known that hydrophobic hemin possesses low catalytic activity in aqueous solution due to dimerization, and the introduction of G4 can form a noncovalent G4/hemin DNAzyme system with HRP-like activity. , Recently, our group reported that covalently anchored hemin at the 3-terminal of G4 was more active than the previous nonconjugated system, , which stimulated us to test whether covalent attachment of hemin to both ends of G4 (3′- and 5′-terminal, denoted as dHemin-G4) would further improve the peroxidase activity of the system. As expected, the catalytic activity of the dHemin-G4 DNAzyme system coupled with hemin at both ends of G4 was significantly higher than that of noncovalent G4/hemin and also was 182 times higher than that of hemin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well-known that hydrophobic hemin possesses low catalytic activity in aqueous solution due to dimerization, and the introduction of G4 can form a noncovalent G4/hemin DNAzyme system with HRP-like activity. , Recently, our group reported that covalently anchored hemin at the 3-terminal of G4 was more active than the previous nonconjugated system, , which stimulated us to test whether covalent attachment of hemin to both ends of G4 (3′- and 5′-terminal, denoted as dHemin-G4) would further improve the peroxidase activity of the system. As expected, the catalytic activity of the dHemin-G4 DNAzyme system coupled with hemin at both ends of G4 was significantly higher than that of noncovalent G4/hemin and also was 182 times higher than that of hemin.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation method of double hemin covalently connected to the both ends of G4 DNA sequence, 5′-CTG­GGT­GGG­TGG­GTG­GGTC-3′, that is, dHemin-G4, was based on a reported method of construction of single covalent linkage of G4 and hemin with minor modifications . Specifically, 1 mL of hemin DMSO solution (1 mM) was mixed with 0.5 mL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N -hydroxysuccinimide (NHS) solution (10 mM each) followed by stirring for 2 h at room temperature to activate the carboxyl group of hemin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal–organic frameworks (MOFs) are an interesting family of hybrid porous polymeric materials assembled by the coordination of metal ions and organic linkers. MOFs have drawn tremendous interdisciplinary interest because of their multiple desirable characteristics, e.g., ultrahigh porosity, tunable pore size, high surface area, adjustable structure, and composition as well as functional diversity. Among numerous MOFs, semiconductor MOFs, e.g., MOF-5, MIL-100­(Fe), UiO-66­(Zr), MIL-125­(Ti), and porphyrinic MOFs, are of particular interest due to their light-harvesting properties. Currently, various semiconductor MOFs and their functional heterojunctions have been explored as advanced materials for specific biomedical applications. Although a promising perspective has been revealed, the full potential of semiconductor MOFs remains largely untapped, especially research concerning their application in bioelectronics and optoelectronics is quite scarce.…”
Section: Introductionmentioning
confidence: 99%